Risk factors and coping strategies of playing-related musculoskeletal disorder (PRMD) in tertiary student pianists: a phenomenological study - Xiaoyu, Miao (Dove Medical Press, 2024)
Purpose: While pianists enjoy the happiness of creating music, they also face many health problems, with playing-related musculoskeletal disorder (PRMD) being one of the most common occupational diseases. Compared with professional pianists, tertiary student pianists are easy to neglect, but they also suffer from playing-related injuries and face many difficulties and challenges. This study aims to investigate the risk factors of student pianists suffering from PRMD and the strategies to cope with PRMD from their lived experience using the method of descriptive phenomenology and the social cognitive theory (SCT) as the theoretical basis. Patients and Methods: This study’s data are derived from semi-structured one-on-one interviews with twelve student pianists at seven higher education institutions in China and are analyzed using Moustakas’ improved Stevick-Colaizzi-Keen (SCK) phenomenological analysis method. Results: This study developed nine themes related to PRMD risk factors and copy strategies within the SCT framework, they are: self-efficacy, personal psychological factor, self-regulation, piano-playing factors, receive medical treatment, outcome expectation, negative effects from social relations, help from social relations and physical environment. Conclusion: The findings identify the profound influences of personal, social, behavioral, and environmental factors on the PRMD-related experiences of tertiary student pianists and highlight the importance of improving the self-efficacy and self-regulation ability of tertiary student pianists, as well as promoting social and healthcare attention and support for them.